Peran Religiusitas dalam Menghadapi Quarter Life Crisis pada Generasi Z - Asfira, Aulia; Sari, Trie Yunita (Faculty of Ushuluddin Syarif Hidayatullah State Islamic University, 2023)
This article explains more clearly the role of religiosity in facing the quarterlife crisis in Generation Z to prove the extent to which religion plays a role in the crisis phase experienced by Generation Z. The method used to analyze answers uses a qualitative-descriptive method. A quarter-life crisis is a crisis phase in a quarter of a year of a person's life who experiences doubts in their life including career, social relationships, academics, and the economy. The results of this research show that religiosity plays a role for Generation Z in recovering from the Quarter Life Crisis phase in different contexts. There are some Generation Z who believe religiosity plays a significant role by believing that religion provides resources for saviors in the Quarter Life Crisis phase that is being experienced. But in another context, other Generation Z stated that religiosity does not play a role without a self-thinking pattern, maximum effort to rise from the phase Quarter Life Crisis, as well as support from those closest environment